Fazlur Rahman dan Interpretasi Teks al-Qur’an - Ahmad Nabil Amir (JOURNAL OF QUR'AN AND HADITH STUDIES, 2021)
This paper examines the framework of Fazlur Rahman (1919-1988) and the interpretations used by him in interpreting the text of the Qur'an which is presented in his book entitled Major Themes of the Qur'an. He also highlighted the basic principles that form the fundamental revisionist and contextual understanding that underlies his methodology in understanding the texts written in several of his books such as his book entitled Islamic Methodology in History, Revival and Reform in Islam: A Study of Islamic Fundamentalism, Prophecy in Islam: Philosophy. and Orthodoxy, and Islam. The basic framework of his interpretive methodology is assembled from historical frames and contextual reviews and thematic readings that outline dynamic principles in understanding texts with strong moral and philosophical interpretations.